(untitled) (Journal of the College of Basic Education, 2022)
The book Al-Bizra or Al-Bizdra is one of the books that dealt with its subject the knowledge of the conditions of the prey in terms of their health and disease, the principles of their upbringing, and the signs of their strength in hunting or their weakness. Stolen books, he is the vizier of the Caliph Nizar Bin Maad Bin Ismail Al Fatimi, the fifth of the Fatimid Caliphs, as he grew up in the shadow of the Caliphate and advanced to the Beazar after twenty years of hunting.The modern descriptive linguistic studies that de Saussure brought have contributed to deepening the stylistic lesson of literature and pushed it to reduce and abolish the abhorrent normativeness and abolish it completely, in order to acquire the status of science. Both linguistics and stylistics have a purely linguistic premise. On the other hand, the stylistic lesson was concerned with the text, which made it distinct and unique, so the text was the basic logic in the process of stylistic analysis and its aesthetic structures.The study was concerned with the content of the investigation of verbal verbs within the science of semantics and its study according to its availability with conscious intention in the text and its dominance over its joints within the narrative description of the text of the book Al-Bizrah and the description of the prey in it.